2016
DOI: 10.1186/s12889-016-3833-z
|View full text |Cite
|
Sign up to set email alerts
|

Residential neighbourhood greenspace is associated with reduced risk of incident diabetes in older people: a prospective cohort study

Abstract: BackgroundThree cross sectional studies suggest that neighbourhood greenspace may protect against incident diabetes. This study uses data from a longitudinal study with a large sample size to investigate the association between greenspace and the occurrence of incident diabetes over time.MethodsData was from the European Prospective Investigation of Cancer Norfolk, UK, cohort, recruitment 1993–2007 (N = 23,865). Neighbourhoods were defined as 800 m circular buffers around participants’ home locations, accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 37 publications
5
58
0
2
Order By: Relevance
“…La muestra reclutada se integró en su mayoría por mujeres, lo que coincide con otros autores (14,16,22) , CC aumentada en mujeres >80 cm y en hombres >94 cm. Se midió con cinta métrica flexible SECA 203.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…La muestra reclutada se integró en su mayoría por mujeres, lo que coincide con otros autores (14,16,22) , CC aumentada en mujeres >80 cm y en hombres >94 cm. Se midió con cinta métrica flexible SECA 203.…”
Section: Discussionunclassified
“…La revisión de literatura pone en evidencia factores individuales como falta de ejercicio, SP/OB, HTA, antecentes familiares de DM22, bajo nivel educativo y económico (14) , ansiedad, depresión (15) , consumo de sustancias psicoactivas (16) , baja percepción de riesgo (17) ; así como factores en diferentes niveles de estructura social como el escaso apoyo social (18) , extensas jornadas de trabajo, estrés laboral (19,20) , inseguridad alimentaria, percepción de problemas comunitarios (21,22) , desarrollo urbano y urbanización (23)(24)(25) el bajo nivel educativo en la comunidad (26) , bajo acceso a la atención en el sistema sanitario (27,28) y la economía local y nacional (29,30) .…”
Section: -51unclassified
“…Information on the study design and setting, exposure to neighbourhood greenspace, physical activity and some of the covariates and confounders has been published previously, as a similar approach to the methods and analyses was used for this study [36]. This study advances previous work by examining a different health outcome, which is an important public health concern linked to modifiable lifestyle behaviours.…”
Section: Methodsmentioning
confidence: 99%
“…Methods used previously [36] were used to define the exposure variable; greenspace coverage (percentage) in the home neighbourhood of the participant. Briefly, the home postcode (zip [40].…”
Section: Exposure To Neighbourhood Greenspacementioning
confidence: 99%
“…A small number of studies have found a reduced risk of type 2 diabetes with higher levels of green space. [156][157][158] A recent meta-analysis of six studies found an overall reduction in risk of diabetes for increasing levels of green space in the pooled analysis. 159 An increased odds of developing diabetes has been seen for areas with lower green space, even when BMI was not related to green space.…”
Section: Diabetesmentioning
confidence: 99%